Chamaejasmine B Induces the Anergy of Vascular Endothelial Cells to VEGFA Pro-angiogenic Signal by Autophagic Regulation of VEGFR2 in Breast Cancer - Li, Qi; Kan, Xiaoxi; Yin, Jie; Sun, Lidong; Wang, Yajie; Li, Yujie; Yang, Qing; Xiao, Hongbin; Chen, Ying; Weng, Xiaogang; Cai, Weiyan; Zhu, Xiaoxin (Frontiers in Pharmacology, 2018)
The neovascularization functions essentially for malignant upgrading and predicts poor prognosis in multiple cancers, which make it the highly effective strategy for clinical treatment. Unfortunately, the known anti-angiogenic therapies show low effectiveness against breast cancer. Recently, rebalancing the pro-angiogenic property in microenvironment shows great advantages and attracts increasing attention for breast cancer treatment. Herein, we for the first time reported that Chamaejasmine B (ICJ), extracted from Stellera chamaejasme L., possessed potent anti-angiogenic effect in breast cancer. By Transwell, tube formation and aortic-ring assays, ICJ efficiently suppressed the neovascularization potential in tumor-HUVEC co-culture model. In Matrigel plug assay, the efficacy of ICJ was further identified in vivo. Mechanistically, with little influence on HUVEC apoptosis, ICJ obviously induced autophagy as proved by the elevated LC3І/ІІ ratio, dotted distribution of LC3 and upregulated Beclin-1. Moreover, by associating with LC3 and in turn, inhibiting the level of VEGFR2, the anti-angiogenesis efficacy was closely dependent on the initiation of autophagy. Above results proved that, by attenuating the pro-angiogenic communication through VEGFR2, ICJ is a novel angiogenic inhibitor and will be a promising supplement for anti-angiogenic chemotherapy for breast cancer.